THE EFFECT OF METHANOGENIC INHIBITOR FEED ON PROPIONIC ACID AND LAMB MEAT CHEMICAL QUALITY - Sondakh, E.H.B.; Yusiati, I.M.; Hartadi, H.; Suryanto, E. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
This study aimed to determine the effect of medium chain fatty acids (MCFA) on propionic acidsand lamb meat chemical quality. The treatment given was R1: feed without medium chain fatty acids(MCFA), while R2 dan R3 were the feed contained 1.0% and 1.5% of MCFA, respectively. The twelveheads of lambs yearling weight of 16-17 kg were used as materials. Biological trial was done for threemonths and then was slaughtered. Before being slaughtered, the animal was taken rumen fluid to beanalyzed for propionic acid. The carcass was sampled to be analyzed for chemical composition,cholesterol and fatty acids content. This study showed that methanogenic inhibitor feed with 1.0-1.5%MCFA could be used as sheep feed, and the results: the propionic acid content in rumen increased 29.59– 36.11%. The cholesterol content decreased 7.14-10.06%. For the meat fatty acids composition,unsaturated fatty acids increased 9.05 – 17.96%. while saturated fatty acid decreased 6.59 – 11.88%.